El relato en las escuelas de “La agresión y derrota de la subversión marxista”. Estudio de caso a través de la asignatura Historia para el 3º año del nivel medio de acuerdo a los Planes y Programas del Ciclo Básico de Contenidos Mínimos de 1979 y los manuales de historia - Fantino, Juan Francisco (Res Gesta, 2022)
Education played a strategic role for governments of Proceso de Reorganización Nacional. Among several actions, in 1979 was carried out Reform Plans and Programs Minimum Contents Basic Cycle (Ministerial Resolution 242/79) for the secondary level. In the third year, the History course established the teaching of “la agresión mundial comunista” and the “proceso de formación occidental”. The reform of contents involved a new generation of textbooks to be a reference to such "aggression" and "struggle." Thus, the following paper analyzes how these contents were presented in history textbooks.